The Role of Students of English Education Study Program at Nias Raya University in Developing Tourism Potential in Nias Island - I Gusti Ayu Agung Dian Susanthi; Yonatan E. Laia (Linguistic Community Services Journal, 2022)
Language became a very essential aspect of human life as a result of the growth of a very large era at this time. Particularly in the usage of English as an international language. However, along with changes and improvements in social, cultural, and economic factors, tourism has also established the tourism sector as one of the most important factors for the global community, particularly for the people of South Nias, which still preserves and presents natural and cultural beauty that remains intact even in the midst of modernity. Of course, the existence of current tourists will elicit a favorable response. Thus, to prevent this from happening, a solution is needed, namely by providing teaching or socialization in the form of training of tour guide for the next generation. The community services program organized by Warmadewa University and Nias Raya University which aim to educate and increase the interest of the younger generation regarding the preservation of the tour guide and the awareness of tourism destination, this also has a relationship with cultural and linguistic aspects. This article used descriptive qualitative methodology to describe real-world occurrences that occur in a community. The data were gathered by observation, interviews, and documentation. As a consequence of this service, the younger generation is interested in tour guide profession in order to preserve one of the world's acknowledged of tourism in Nias Island especially for the students of English language study program at Universitas Nias Raya.